2010
DOI: 10.2165/11317690-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Performance of the ‘Minto’ Remifentanil Pharmacokinetic Parameter Set in Morbidly Obese Patients Ensuing from a New Method for Calculating Lean Body Mass

Abstract: The median values (interquartile ranges) of the MDPE, MDAPE, divergence and wobble for the James equations during maintenance were -53.4% (-58.7% to -49.2%), 53.4% (49.0-58.7%), 3.3% (2.9-4.7%) and 1.4% h(-1) (1.1-2.5% h(-1)), respectively. The respective values for the Janmahasatian equations were -18.9% (-24.2% to -10.4%), 20.5% (13.3-24.8%), 2.6% (-0.7% to 4.5%) and 1.9% h(-1) (1.4-3.0% h(-1)). The performance (in terms of the MDPE and MDAPE) of the corrected pharmacokinetic set was better than that of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 13 publications
0
17
0
2
Order By: Relevance
“…When the LBM derived from this equation is graphed against BW, an inverted parabolic function is created (13). Therefore, the LBM values start to decrease after a critical weight, leading to what is likely an underestimation of LBM and an undercorrection of SUV in obese patients (11).…”
Section: Discussionmentioning
confidence: 99%
“…When the LBM derived from this equation is graphed against BW, an inverted parabolic function is created (13). Therefore, the LBM values start to decrease after a critical weight, leading to what is likely an underestimation of LBM and an undercorrection of SUV in obese patients (11).…”
Section: Discussionmentioning
confidence: 99%
“…However, in a follow-up study, the same authors showed a better predictive performance of the same PK parameters when the Janmahasatian equations were used. 19…”
Section: Lean Body Weightmentioning
confidence: 99%
“…As clearance is the most relevant pharmacokinetic parameter for maintenance dosing, LBW is a more relevant dosing scalar than TBW for those drugs whose clearance is linearly correlated to LBW. 3 Values obtained by the Janmahasatian equation are more accurate and have been validated with comparison to values obtained by bioimpedance scales. Dual x-ray absorptiometry, bioimpedance scales, and air/water displacement tanks remain the most accurate tools for calculating body composition.…”
Section: Increase In Body Weight and Changes In Body Compositionmentioning
confidence: 75%